Recent advances of carbon dots as new antimicrobial agents. Issue 2 (20th June 2022) - Li, Pengfei; Sun, Lu; Xue, Shanshan; Qu, Dan; An, Li; Wang, Xiayan; Sun, Zaicheng
Abstract: Due to the COVID‐19 pandemic, many rapid antimicrobial agents have developed intensively. Carbon dots (CDs), a new type of carbon‐based nanomaterials, shows great potential against emerging infectious diseases and antimicrobial‐resistant infections due to their unique optical properties, excellent biocompatibility, and easy surface modification. With the definition of the CDs structure and properties, synthesis, and characteristic technology improvement, the research on the CDs as antimicrobial agents has made significant progress. However, the lack of high repeatable and exact preparation methods, and the regular antimicrobial activity make it far from practical application. In this review, we summarize the most recent progress and challenges of CDs antimicrobial. First, an overview of the characteristics and properties is given, and the advantage of CDs applied to antimicrobial is further discussed. Then, it focuses on research progress on antimicrobial mechanisms under different conditions, the critical factors affecting their antimicrobial activity, and the practical antimicrobial applications. Finally, the main challenges and future research perspectives of antimicrobial CDs are proposed. Abstract : This review summarizes the most recent progress and challenges of carbon dot (CDs) antimicrobial, discusses the antimicrobial mechanisms under different conditions, the critical factors affecting their antimicrobial activity, and the practical antimicrobial applications. Finally, the main challenges and future research perspectives of antimicrobial CDs are proposed.